Efektivitas Edukasi Gizi Berbasis Pangan Lokal dalam Meningkatkan Pengetahuan dan Kesadaran Siswa SMP, Kabupaten Lembata, Nusa Tenggara Timur - Syarif Hidayatullah; Nabilla A. Suryono; Victorian H. Azizi; Indri Amelia; Ummi Rohimah; Nova A. Ramadhani; Riyo T. P. Dewanni (Universitas Muhammadiyah Semarang, 2025)
Balanced nutrition is the main foundation for optimal growth and development of school-age children, which affects their physical health, cognitive abilities, and academic achievement. In Indonesia, nutrition is still a crucial issue, especially in areas with low economic levels such as Wulandoni District, Lembata Regency, East Nusa Tenggara. This study aims to measure the effectiveness of local food-based nutrition education (PGS-PL) in increasing students' knowledge and awareness of balanced nutrition at SMP Negeri 1 Wulandoni. The research methodology included initial assessment, socialization, preparation of educational materials, implementation of education through interactive presentations, ice breaking activities, and demonstration of tempeh making, followed by evaluation using pre-test and post-test. The results showed a significant increase in students' understanding of the concept of balanced nutrition and local food consumption, with an increase in active participation from 30% in the pre-test to 35% in the post-test. Interactive activities and rewards successfully increased student engagement and motivation. Nonetheless, the implementation of the activities faced several challenges, including schedule delays, limited participants, delays in preparation, as well as logistical issues such as power outages and weather conditions. The conclusion of this study confirms that local food-based educational interventions are effective in improving students' understanding of balanced nutrition and recommends the development of similar programs in other schools, with improved planning and coordination to overcome the obstacles encountered. This study makes a significant contribution to the literature on nutrition interventions in school settings and offers practical guidance for stakeholders in designing more effective and sustainable nutrition programs.